Pelaksanaan Ketentuan Hak Merek Sebagai Objek Jaminan Kredit Pada Bank Perkreditan Rakyat (BPR) di Kota Denpasar - Dewa Ayu Dita Novilina; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2021)
A brand right is a type of intellectual property consisting of an unrecognizable sign which is regulated in Article 499 of the Civil Code. The study's concern in this thesis is how the regulation is implemented of brand rights as an object of credit collateral in Bank Perkreditan Rakyat? And how is the implementation of provisions on brand rights as an object of credit collateral in Bank Perkreditan Rakyat in Denpasar City? The research method in this thesis used an empirical legal research method. The factual approach in the field (interview) and legislation were employed in this study. The conclusion of this thesis is the usage of the trademark as a bank credit collateral is regulated in Law Number 20 of 2016 Concerning Marks and Geographical Indications Article 41 which stated that rights to registered marks may be transferred or transferred by agreement. The implementation of brand rights usage as an object of credit guarantee in Bank Perkreditan Rakyat has never happened in Denpasar city. This is caused by the brands that are difficult to predict in nominal and brand rights that are less marketable.